Determinants of employer-provided further training: A multi-level approach - Lutz Bellmann; Christian Hohendanner; Reinhard Hujer (Institute for the Study of Labor (IZA), 2010)
We analyse the influence of regional determinants on the decision of employers to provide within-firm further training. We estimate the effects of the regional population density, the unemployment rate and the regional concentration of an industry against the background of several determinants of further training at the establishment level. To account for the clustered and longitudinal structure of our data - with annual observations of firms and firms nested within regions - we apply multi-level random effects logit models. Our empirical analysis is based on the IAB-Establishment Panel 2001 to 2007.
Keywords: J24; I21; C33; R12; 330; multi-level panel analysis; human capital; further training; regional labour markets